The effectiveness of using direct marketing on private hospital: a case study of Putra Specialist Hospital Melaka Sdn Bhd / Nurul Syazwani Zakaria - Zakaria, Nurul Syazwani (2017)
Direct marketing is one of the advertising which use by the business to communicate with the customers or people directly to promote the product or services that being offered and the effectiveness of the use of it can ensure the message of every details and information of the product and services can be delivered successfully to the customers. Direct marketing includes direct mail, face to face selling, internet marketing, catalogues, telemarketing, direct-response advertising and kiosk marketing. Direct marketing is practiced by businesses of all sizes, A direct advertising campaign aims to deliver a good return on investment by showing how many potential customers responded to a clear call to action. By using the direct marketing can create awareness towards the business.